Pengaruh Larangan Ekspor Bahan Baku terhadap Kinerja Perusahaan Rotan Indonesia - Damayati, Ashintya; Nachrowi, Nachrowi D. (Jurnal Ekonomi dan Pembangunan Indonesia, 2013)
This research analyzes the impacts of raw material export restriction on firm performance: value-added, labor, and productivity growth, as well as firm survival ability in the rattan-based final good industry in the 1995-2004 period, which are distinguished based on firm size. This study uses probit method for the survival model, and the Ordinary Least Square (OLS) for the growth model. Data obtained from Medium and Large Scale Industries Statistics (ISIC 33131 and 33212). The result shows that export restriction can improve survival ability of the medium and large-sized firm, and have a positive impact on value-added and labor growth of the medium-sized firm.